PENERAPAN LESSON STUDY UNTUK MENINGKATKAN KEMAMPUAN PENGELOLAAN KELAS DAN HASIL BELAJAR KOGNITIF DIKELAS VIII-J SMPN 2 TARAKAN PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN SERTA PEMANFAATANYA DALAM TEKNOLOGI - Lisdawati Silaban; Rita Hayati (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2020)
Abstract: The implementation of the 2013 Curriculum at SMP Negeri 2 Tarakan requires teaching staff to always be active and creative in class processing with the aim that students' cognitive learning outcomes increase in accordance with predetermined minimum grade completeness standards. Based on this, the existence of teachers to manage an optimal and conducive classroom is needed. One of the efforts made by the teacher in improving the ability to manage the class and students' cognitive knowledge is by implementing lesson study activities. The type of research used is lesson study-based action research using a qualitative descriptive approach. The class used as research was VIII-J which was observed by 3-5 observers using 4 cycles. Based on the data analysis and discussion that has been done, the results obtained are: 1) the implementation of lesson study from the plan, do, and see stages has increased from lesson study I to IV with an average of 93% in the very accomplished category; 2) The ability to manage the classroom by the model teacher through the implementation of lesson study obtained an average score of 76.5% in the good category; 3) The development of the ability to manage the classroom by the model teacher through the implementation of lesson study in relation to student learning outcomes has increased. Keywords: lesson study, manage the class, cognitive knowledge